Retrospective on molecular assay design for detecting pan-orthopox viruses and prospective on mpox laboratory preparedness and readiness - Yeh, Kenneth B.; Powers, Michael D.; Patel, Ami; Parekh, Falgunee; Tseng, Ashley S.; Bradford, Elaine; Parker, Kyle; Soong, Ricky; Olinger, Gene; Mombo, Illich (Frontiers in Tropical Diseases, 2023)
The landscape of in vitro diagnostic (IVD) devices encompasses a broad range of tests that have been used to detect and diagnose pathogens, especially tropical diseases, for decades. The COVID-19 pandemic exemplified the greater need for bringing IVDs from the laboratory directly to the consumer, and recent outbreaks such as mpox, Sudan ebolavirus, and Marburg virus further reinforce this need. The increased emergence of tropical disease outbreaks requires more agile development, higher performance, and mass production of IVD devices. Furthermore, lessons learned in previous device developments can sometimes be used to accelerate new disease diagnostic applications. As an example, we describe one case history of an earlier pan-orthopox viral assay that detected smallpox variola and vaccinia strains, and also discerned related strains including mpox. This work established the foundation for the molecular detection of orthopox viruses, which could be mobilized to address public health needs once an emergency declaration was made that opened the FDA pathway for issuing an emergency use authorization for the use of these assays. Thus, the utilization of knowledge from earlier investments was shown to enhance preparedness and readiness. Here in this retrospective, we elaborate on the processes that enable this approach, including multi-disciplinary and multisectoral collaborations to accomplish a holistic, one health world.